Implementasi Evaluasi Pembelajaran Al-Qur’an Hadis Berbasis Learning Management System di MTs Al-Muttaqin - Syahputra Lubis, Amru; Tanjung, Alfian; Piliang, Fenny Mustika (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the implementation of Learning Management System (LMS)-based evaluation in Al-Qur’an Hadith learning at MTs Al-Muttaqin, focusing on evaluation planning, implementation processes, and the supporting and inhibiting factors affecting its implementation. This research employs a qualitative descriptive approach. The informants consist of the head of the madrasa, Islamic Education (PAI) teachers, and students. Data collection techniques include observation, interviews, and documentation. Data analysis uses the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. Data validity is ensured through source and method triangulation. The findings show that LMS implementation in learning evaluation has been initiated but remains at an early stage and is not yet optimal. LMS is used for assignments, online quizzes, task submission, and digital grading; however, it is still limited to the cognitive domain. Evaluation planning has not been systematically integrated with LMS, and its implementation faces several challenges. Supporting factors include institutional support, availability of technological facilities, and students’ enthusiasm, while inhibiting factors include unstable internet access, low digital literacy, limited devices, and lack of training. This study concludes that effective LMS implementation requires improved teacher competence, adequate infrastructure, and more systematic integration to ensure effectiveness and sustainability.